2023
DOI: 10.1002/adma.202209814
|View full text |Cite
|
Sign up to set email alerts
|

Dislocated Bilayer MOF Enables High‐Selectivity Photocatalytic Reduction of CO2 to CO

Abstract: Scheme 1. Schematic diagram of the synthetic routes for preparing monolayer MOF and bilayer MOF.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
27
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 103 publications
(44 citation statements)
references
References 91 publications
0
27
0
Order By: Relevance
“…Particularly, Pt-SA/TT exhibited the highest photocatalytic activity of 20.5 µmol g −1 h −1 with a high selectivity of 96%, which was attributed to the synergistic effect of atomic interface engineering of single-atom Pt and interfacial TiOTi for effective charge separation. The high CO selectivity could be ascribed to the thermodynamically favored adsorption of CO 2 and the desorption of *CO. [45,46] Moreover, the photocatalytic performance of Pt-SA/TT for CO 2 reduction is higher than or comparable to that of the recently reported TiO 2 -based photocatalysts (Table S4, Supporting Information). In comparison, when Pt nanoparticles were loaded, the photocatalytic performance decreased due to the poisoning of Pt by carbon monoxide or the strong adsorption of intermediates, further revealing the critical role of atomically dispersed Pt in promoting the CO 2 reduction reaction.…”
Section: Resultsmentioning
confidence: 48%
“…Particularly, Pt-SA/TT exhibited the highest photocatalytic activity of 20.5 µmol g −1 h −1 with a high selectivity of 96%, which was attributed to the synergistic effect of atomic interface engineering of single-atom Pt and interfacial TiOTi for effective charge separation. The high CO selectivity could be ascribed to the thermodynamically favored adsorption of CO 2 and the desorption of *CO. [45,46] Moreover, the photocatalytic performance of Pt-SA/TT for CO 2 reduction is higher than or comparable to that of the recently reported TiO 2 -based photocatalysts (Table S4, Supporting Information). In comparison, when Pt nanoparticles were loaded, the photocatalytic performance decreased due to the poisoning of Pt by carbon monoxide or the strong adsorption of intermediates, further revealing the critical role of atomically dispersed Pt in promoting the CO 2 reduction reaction.…”
Section: Resultsmentioning
confidence: 48%
“…[14][15][16] As a consequence, organic dyes in dye-based MOFs are often used as photosensitizers for photocatalytic hydrogen production and CO 2 reduction, which does not make sufficient use of the redox properties of organic dyes, thereby limiting the application of MOFs as photocatalysts. [17][18][19][20][21][22] Taking advantage of the easy modification features of MOFs, introducing the functional groups within MOFs is a promising and effective strategy for tailoring the physical environment of cavities, pores and electronic structures for tar-geted applications. [23][24][25] Recent research has indicated that the functionalization of dye-based ligands can regulate the twisted conjugative junction between the ligands and metal nodes, which enables MOFs to markedly enhance the separation efficiency of photogenerated carriers in MOFs and hamper the futile intramolecular fluorescence quenching, thus enhancing the photocatalytic efficiency.…”
Section: Introductionmentioning
confidence: 99%
“…Reducing the atmospheric concentration of carbon dioxide (CO 2 ) for mitigating the greenhouse effect is crucial as it is emitted excessively due to the combustion of fossil fuels. The solar-light-driven conversion of CO 2 into valuable derivatives, including CO, CH 4 , and HCOOH, is among the most promising CO 2 conversion pathways. However, the photocatalytic reduction of CO 2 is currently inefficient because the extremely stable chemical bonds of CO 2 (CO, 750 kJ mol –1 ) caused difficulty of CO 2 adsorption and activation and competitive reactions of water reduction in the aqueous phase. , It is evident that the hydrogen evolution reaction (HER) is more favorable thermodynamically due to the less negative redox potential required through a comparison of the reduction reaction process for CO 2 to CO and water to hydrogen (CO 2 + 2H + + 2e – → CO + H 2 O, E 0 = −0.52 V vs NHE or 2H + + 2e – → H 2 , E 0 = −0.42 V vs NHE). Furthermore, the water-insoluble CO 2 molecules pose a greater challenge in terms of contacting the catalyst compared to the water molecules, which exacerbates the over-reaction of water decomposition and leads to the low efficiency of CO 2 reduction. Therefore, enhancing the adsorption and activation of CO 2 while suppressing the occurrence of HER during photocatalytic CO 2 reduction are viable approaches for improving both the catalytic activity and selectivity of CO 2 reduction.…”
Section: Introductionmentioning
confidence: 99%